2005
DOI: 10.1177/08830738050200020901
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Changes in Children Treated for Acute Lymphoblastic Leukemia With Chemotherapy Only According to the Pediatric Oncology Group 9605 Protocol

Abstract: The purpose of this study was to examine cognitive functioning and neuroimaging in children with leukemia treated with the Pediatric Oncology Group 9605 protocol at the Children's Hospital of Eastern Ontario. Mean age at diagnosis was 4.88 +/- 2.54 years. The mean (n = 24) Wechsler Verbal and Performance IQ fell in the low-average range (87.33 +/- 15.69 and 84.83 +/- 19.11, respectively). Mean (n = 20) Verbal and Visual Memory Indexes of 82.95 +/- 15.46 and 88.30+/- 10.80, respectively, were obtained. The prop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
53
0
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(56 citation statements)
references
References 15 publications
2
53
0
1
Order By: Relevance
“…Montour-Proulx et al [2005] reported leukoencephalopathy in 78% of 23 children treated on POG 9605. Acute WM abnormalities may be transient; in some cases, they improve significantly following completion of treatment [Harila-Saari et al, 1998;Reddick et al, 2005a,b].…”
Section: Neuroimaging and Neurocognitive Outcomesmentioning
confidence: 95%
See 1 more Smart Citation
“…Montour-Proulx et al [2005] reported leukoencephalopathy in 78% of 23 children treated on POG 9605. Acute WM abnormalities may be transient; in some cases, they improve significantly following completion of treatment [Harila-Saari et al, 1998;Reddick et al, 2005a,b].…”
Section: Neuroimaging and Neurocognitive Outcomesmentioning
confidence: 95%
“…Acute WM abnormalities may be transient; in some cases, they improve significantly following completion of treatment [Harila-Saari et al, 1998;Reddick et al, 2005a,b]. The instability of WM abnormalities results in poor correlations with neurocognitive findings in children on active treatment [Wilson et al, 1991;Montour-Proulx et al, 2005] and the implications of these early transient imaging abnormalities for long-term neurocognitive functioning are unknown.…”
Section: Neuroimaging and Neurocognitive Outcomesmentioning
confidence: 95%
“…Both of these findings are consistent with our own experience in which acute neurologic toxicity is most often associated with IT-MTX, and chronic neurotoxicity such as decreased cognitive functioning is more likely associated with IV-MTX and LE. Montour-Proulx et al [84] found that children treated with chemotherapy alone on the POG9605 protocol experienced substantial adverse effects on intelligence and memory functioning: 78% of 23 subjects showed LE on at least one MR image.…”
Section: Neurocognitive Impact Of Antileukemia Therapymentioning
confidence: 99%
“…In the pediatric brain tumor population, deficits seen with chemotherapy treatments are less than those seen with radiation. Nonetheless, specific chemotherapies such as methotrexate have previously demonstrated deleterious effects on neurocognition and chemotherapy, as a whole, has been linked to deficits in executive functioning, attention, visualmotor functioning, visual processing and overall IQ in children treated for leukemia [45,46,47]. Interestingly, a study done by Meyers and Hess, found that decreases in cognition preceded tumor progression on imaging in adult patients with brain tumors [48].…”
Section: Neurocognitive Outcomesmentioning
confidence: 99%